Research on dynamic response characteristics of normal fault footwall working face and rock burst prevention technology under the influence of the gob area - Lianhai Tai; Chong Li; Shitan Gu; Xiaoxiao Yu; Zhijun Xu; Lei Sun (Scientific Reports, 2023)
Abstract To study the effect of mining dynamic response characteristics on the footwall working face of the normal fault under the influence of the gob area, theoretical research, indoor experiment, and numerical simulation are adopted to analyze the stress manifestation characteristics, overburden movement, and energy evolution characteristics during the process of mining. The results show that: (1) In the process of mining toward the fault, the working face shows the change characteristics of “stable-activation mutation-final stability”. At 20 m from the fault, the arch structure of the working face was damaged, fissures appeared near the high fault fracture zone, and the displacement of the overburden rock increased significantly; (2) the maximum value was reached at 4–8 m from the coal wall, and the superposition of tectonic stress and mining stress led to the concentration of the stress and energy accumulating on the top plate near the fault, and the data close to the gob area were even larger; (3) If the plastic damage zone of the high-level rock layer on the hanging wall and footwall of the fault appears to have a wide range of penetration, and the area formed between the shear displacement curve of the fault plane and the X-axis appears to have a significant enhancement, it is considered that the fault has been activated; (4) The size of the coal pillar of the fault is determined to be 40 m, and combined with the pressure unloading technique of the variable-diameter drilling hole, the validation is carried out through the micro-vibration monitoring, and the results of which can be used as a reference for the safety of the working face under similar conditions.